A novel solar thermal system combining with active phase-change material heat storage wall (STS-APHSW): Dynamic model, validation and thermal performance. (15th June 2020) - Li, Han; Li, Jinchao; Kong, Xiangfei; Long, Hao; Yang, Hua; Yao, Chengqiang
Abstract: Due to the energy shortage and air pollution caused by heating emissions, solar energy becomes the first choice for clean heating in China. On this basis, a novel solar thermal system coupling with active phase-change material heat storage wall (STS-APHSW) is proposed in this study. And the thermal performance of STS-APHSW is numerically explored by one transient heat transfer model combined with TRNSYS. Taking indoor temperature as the evaluation index, the effect of the solar collector area, hot water flow rate, initial melting temperature and thickness of phase change material energy storage wallboard (PCMSW) on the indoor temperature maintained by STS-APHSW is discussed and analyzed. Economic comfort ratio is proposed to be as the assessment criteria. Results show that the optimal configuration is achieved when: the solar collector area per square unit building area is 0.024 m 2, hot water flow rate is 2.8 kg/s, initial melting temperature is 27 °C and the thickness of PCMSW is 20 mm. This study proves that STS-APHSW can well balance the time mismatch between the solar supply and demand, thus increasing the solar fraction and solar energy application potential in the clean heating. Highlights: A novel solar thermal system coupling with phase-change material was proposed. The thermal performance of the proposed system was numerically investigated. And the optimal configuration of it was obtained by numerical modelling. Our findings provided guidelines for employing the novel system in clean heating.